Ethical overview of health research with regard to the protection of personal health data - Banu Gökçay; Berna Arda (Türk Kardiyoloji Derneği Arşivi, 2019)
Retrospective file research is very common in daily medical practice. Approval is required under current law for the review of personal genetic data, and the informed consent of all research subjects is necessary before conducting non-prospective research. In this article, the protection of personal data will be reviewed within the context of informed consent, the protection of confidentiality, the use of good anonymization techniques, research ethics, and medical law.